Effect of seasonal variability on the development and application of a novel Multimetric Index based on benthic macroinvertebrate communities – A case study from streams in the Karun river basin (Iran). (February 2023) - Esmaeili Ofogh, Ali Reza; Ebrahimi Dorche, Eisa; Birk, Sebastian; Bruder, Andreas
Highlights: Macroinvertebrate-based MMIs are a valuable tool for bioassessment in the Karun River. Seasonal variability affects the MMIs' core metrics composition and MMI performance. Using seasonal MMIs is the best strategy to tackle seasonality in the Karun. MMIs developed during the base-flow period (summer and autumn) had best performance. Abstract: Using multimetric indices (MMIs) for monitoring the ecosystem health of rivers is common practice. Increasing the applicability of MMIs needs understanding of the impacts of natural spatial and temporal variability on community structure in relation to effects of anthropogenic pressure gradients. In this study, we tested the impact of seasonal variability in environmental conditions and macroinvertebrate community structure on the development and application of MMIs using streams in the Karun river basin as a case study. We sampled and measured physical and chemical variables, physical habitat characteristics, and macroinvertebrate communities from 53 stream sites during four seasons. We defined pressure gradients for each season and also by combining all seasons' data. Then, we assessed the applicability of three strategies recommended for tackling the effect of seasonal variability on MMIs development and application: (i) by developing seasonal MMIs (MMIspr, 1 MMIsum, 2 MMIaut, 3 MMIwin 4 ), (ii) by aggregating data across seasons (MMIcomb 5 ), and (iii) by using the signal-to-noise ratio (MMIS/N 6 ). Our results showed that high seasonal variability in the streams of the Karun river could affect the MMIs' core metrics composition and performance. Developing seasonal MMIs was the best strategy to tackle the seasonal variability as indicated by highest precision of MMIs, responsiveness to anthropogenic pressure gradient and sensitivity to impairment. Based on the results of this study, seasons with base-flow (summer and autumn) were most suited for the development of MMIs. The main reason might be the stability in natural drivers (e.g., stable river flows) shaping macroinvertebrate community structure during these seasons. In general, our results showed the MMIs developed based on macroinvertebrate communities could efficiently discriminate reference sites from the impacted sites and, therefore, can be used as a valuable tool for bioassessment in the streams of the Karun river basin and similar systems.